Practice Makes Perfect? The Practice Approach in E-Learning - Friesen, Norm (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRÉPUQ, 2009)
Anyone involved in e-learning is certain to have run across the word practice in connection with a number of notable expressions or phrases: communities of practice, best practices, and teaching practices among others. However, there have been few definitions or discussions that address exactly what practice is. This article provides a short overview of the practice approach, focusing first on its origin in the philosophy of Heidegger and the sociology of Bourdieu. It then provides and analyzes examples of everyday conversational practices, exploring how computer technology can work with (or against) the unscripted, improvisational nature of practice. In this way, this article illustrates both how and why this approach can be valuable for research in e-learning.